Chrysin serves as a novel inhibitor of DGKα/FAK interaction to suppress the malignancy of esophageal squamous cell carcinoma (ESCC) - Jie Chen; Yan Wang; Di Zhao; Lingyuan Zhang; Weimin Zhang; Jiawen Fan; Jinting Li; Qimin Zhan (Elsevier, 2021)
Among current novel druggable targets, protein-protein interactions (PPIs) are of considerable and growing interest. Diacylglycerol kinase α (DGKα) interacts with focal adhesion kinase (FAK) band 4.1-ezrin-radixin-moesin (FERM) domain to induce the phosphorylation of FAK Tyr397 site and promotes the malignant progression of esophageal squamous cell carcinoma (ESCC) cells. Chrysin is a multi-functional bioactive flavonoid, and possesses potential anticancer activity, whereas little is known about the anticancer activity and exact molecular mechanisms of chrysin in ESCC treatment. In this study, we found that chrysin significantly disrupted the DGKα/FAK signalosome to inhibit FAK-controlled signaling pathways and the malignant progression of ESCC cells both in vitro and in vivo, whereas produced no toxicity to the normal cells. Molecular validation specifically demonstrated that Asp435 site in the catalytic domain of DGKα contributed to chrysin-mediated inhibition of the assembly of DGKα/FAK complex. This study has illustrated DGKα/FAK complex as a target of chrysin for the first time, and provided a direction for the development of natural products-derived PPIs inhibitors in tumor treatment.